Strategi Pengembangan Umkm Berbasis Ekowisata Dalam Meningkatkan Pendapatan Masyarakat - Dewi Lestari; Muhamad Ali; Muhamad Juaini; Nadi Atma Sholihah (CIRCULAR: Jurnal Pendidikan Sosial dan Ekonomi, 2026)
This study aimed to analyze the development strategies of Micro, Small, and Medium Enterprises (MSMEs) based on ecotourism in enhancing community income at Bale Mangrove Tourism, Jerowaru Village, Jerowaru District, East Lombok Regency. The study employed a qualitative approach with a case study design, involving MSME actors, tourism managers, and local communities as informants. Data were collected through interviews, observations, and documentation, and were then analysed descriptively. The findings indicated that MSME development strategies were implemented through improving product quality, strengthening entrepreneurial capacity, promoting through digital platforms, fostering collaboration with tourism managers, and utilizing environmental potential as the main attraction. Supporting factors for development included favourable natural conditions, government support, collaboration with tourism managers, and community participation. Meanwhile, the challenges encountered consisted of limited capital, lack of product innovation, and suboptimal market access. The strategies implemented had proven to generate positive impacts on increasing community income, as evidenced by the growth in the number of MSMEs, the increase in business turnover, and the creation of new job opportunities